Concepts of Life and Death in Shakespeare’s ‘Hamlet’ - Cirovic, Mirka (Eikón / Imago, 2021)
No Dane of flesh and bone has been written so devoutly about as Hamlet, which is why he has lived the fate of only a few literary heroes who exist independently of texts and theatre. The tragic hero has become a metaphor in himself, which is why I will attempt to read and interpret Hamlet through the prism of conceptual metaphor theory. My prime interest will be invested in metaphorical representations of life and death perceived as target domains in the process of mapping. It is preoccupation with these abstract notions that gives somber color to the play, defines its mood of nihilism and disillusionment. Hamlet is the play with a high number of references to life, death, the afterlife, and human purpose so that metaphorical linguistic expressions that deal with these themes become corpus for the analysis in this paper. Conceptual metaphor analysis will reveal profound meanings of the selected lines, which are to be found beneath the level of language and syntax, in the sphere where conceptualization of the abstract occurs. Conceptual metaphor analysis may also help us get closer to Shakespeare the man since his unlimited consciousness is, at least to some extent, translated into Hamlet.